The role of self-efficacy and psychological resilience in overcoming occupational stress and enhancing work engagement: a comprehensive structural model in Arab academia - Zayed, Ahmed Mohamed Ahmed; Suliman, Mohamed MohamedEl-Hadi Hassan; Bani AlRasheedy, Benayan; Mohamed Gab Allah, Abdullah Sayed; Hassan, Hassan Mohamed Riad Mohamed; Adam, Halima Mohamed Ibrahim (Frontiers in Education, 2026)
BackgroundGrounded in Bandura’s Social Cognitive Theory and Job Demands-Resources Model, the current study investigates the interaction between self-efficacy and psychological resilience in countering work-related stress and enhancing work engagement amongst teaching staff at Arab universities.MethodologyData collection used a cross-sectional sample of 266 scholars from 7 Arab universities. In this research, an advanced Partial Least Squares Structural Equation Modeling technique was used to examine the complex interrelations between self-efficacy, psychological resilience, occupational stress, and work engagement.ResultsThe model accounted for 39% variance in work engagement (R2 = 0.39). Self-efficacy directly impacted work engagement, whereas both direct and indirect effects were found in the case of psychological resilience upon this construct. Occupational stress acted as partial mediator in the path between psychological resilience and work engagement. There also existed significant gender differences within the model path specifically in the interaction between self-efficacy and work engagement and between psychological resilience and work engagement and the related mediating and moderating roles played by occupational stress.ConclusionPsychological resilience and self-efficacy are key personal resources for academics, but their effects are context-dependent. Therefore, gender differences must be taken into account when designing interventions for the promotion of these resources in academic settings.